Characterization of Metronidazole-Resistant Giardia intestinalis Lines by Comparative Transcriptomics and Proteomics - Krakovka, Sascha; Ribacke, Ulf; Miyamoto, Yukiko; Eckmann, Lars; Svärd, Staffan (Frontiers in Microbiology, 2022)
Metronidazole (MTZ) is a clinically important antimicrobial agent that is active against both bacterial and protozoan organisms. MTZ has been used extensively for more than 60 years and until now resistance has been rare. However, a recent and dramatic increase in the number of MTZ resistant bacteria and protozoa is of great concern since there are few alternative drugs with a similarly broad activity spectrum. To identify key factors and mechanisms underlying MTZ resistance, we utilized the protozoan parasite Giardia intestinalis, which is commonly treated with MTZ. We characterized two in vitro selected, metronidazole resistant parasite lines, as well as one revertant, by analyzing fitness aspects associated with increased drug resistance and transcriptomes and proteomes. We also conducted a meta-analysis using already existing data from additional resistant G. intestinalis isolates. The combined data suggest that in vitro generated MTZ resistance has a substantial fitness cost to the parasite, which may partly explain why resistance is not widespread despite decades of heavy use. Mechanistically, MTZ resistance in Giardia is multifactorial and associated with complex changes, yet a core set of pathways involving oxidoreductases, oxidative stress responses and DNA repair proteins, is central to MTZ resistance in both bacteria and protozoa.